2003
DOI: 10.3168/jds.s0022-0302(03)73969-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in Body Muscle and Fat in Transition Dairy Cattle Fed Differing Amounts of Protein and Methionine Hydroxy Analog

Abstract: The objectives were to determine effects of prepartum protein intake and dietary amino acid balance on production, adaptations in body fat and protein, amino acid concentrations, and, indirectly, body protein breakdown in early lactation. Multiparous Holstein cows (n = 42) were fed diets containing 11 or 14% crude protein with or without 20 g/d of methionine hydroxy analog for 21 d prepartum and then fed a common diet of 17% crude protein for 120 d postpartum, with or without 50 g/d of methionine hydroxy analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
3
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 38 publications
4
46
3
1
Order By: Relevance
“…Therefore, in addition to the negative energy balance, cows are in a negative nitrogen balance in early lactation (Plaizer et al, 2000). Phillips et al (2003) have suggested that the breakdown of muscle protein to provide amino acids for production of milk protein is a mechanism of the normal metabolic adaptation to the high nutrient demand typical of the early lactation. Moreover there can be a redistribution of protein away from carcass toward tissues that support lactation, i.e., gastro intestinal tract and mammary gland (Andrew et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to the negative energy balance, cows are in a negative nitrogen balance in early lactation (Plaizer et al, 2000). Phillips et al (2003) have suggested that the breakdown of muscle protein to provide amino acids for production of milk protein is a mechanism of the normal metabolic adaptation to the high nutrient demand typical of the early lactation. Moreover there can be a redistribution of protein away from carcass toward tissues that support lactation, i.e., gastro intestinal tract and mammary gland (Andrew et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…TG is used for making milk fat by mammary gland during lactation period 4 ; therefore, TG serum concentration is lower in lactation than dry period 23 . On the other hand, At their recent study, Phillips et al 25 demonstrate that inclusion of methionine into diets of cows drops off their serum TG at postpartum 1 st week. By contrast, the studies using methionine during early lactation period report no change in serum TG levels 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, methionine supplementation during periparturient period in cows is reported not to affect normal concentration of NEFA 25 . In the present study, we observed statistically significant changes in serum NEFA concentrations according to all sampling days in all groups (Table 4).…”
mentioning
confidence: 99%
See 2 more Smart Citations